Study on Air Bacteria at Different Altitudinal Locations in Tezpur to Tawang Axis - Chatterjee, Soumya; Datta, Sibnarayan; Banu, Leeza; Vairale, Mohan G.; Sharma, Sonika (Defence Life Science Journal, 2020)
Microflora plays an important role in modulating environmental quality. Among microflora, bacteria are omnipresent in the environment. Pathogenic bacteria, present in air, are known to affect significantly the health and well-being of human, animal or plant populations. Air bacteria monitoring is thus essential for surveillance of pathogenic microorganisms from public health perspective besides its significant implications in detection and mitigation of biothreat related issues. Despite the geo-politically strategic importance of northeast India, there is scarcity of data on human health and disease surveillance. Considering these facts, we, for the first time studied the bacterial diversity of air at six important sites adjacent to the international border in the northeast region of India, having an altitude range of 73 m (Tezpur) to 4170 m (Sela Pass) above sea level. Standard microbiological techniques, such as Tryptone Soya Agar, Mannitol salt and McConkey agar strips and plates were used for air bacterial load assessment and culture for subsequent analysis using biochemical and molecular techniques. Following RFLP study, twenty six different bacterial colonies were isolated. Subsequently, bacteria identification was carried out by examining the substrate utilisation patterns, sequencing 16S rRNA gene and phylogenetic analysis. Results of the study reveal that the isolates mostly belong to two genera Bacillus and Staphylococcus (eleven in each genus), along with Micrococcus, Pseduomonas and Acinetobacter. Based on significant match of our sequences with that of medically important bacterial 16S rRNA sequences available at 16SpathDB 2.0 and review of available literature, we found that a number of these bacterial species have the pathogenic potential. In this manuscript we report our results and discuss the importance of air bacterial surveillance from the perspective of human health, hygiene and biothreat mitigation.